Association of Birthweight with Overweight, Obesity, and Blood Pressure among Adolescents - Hui Fan; Tao Guan; Xingyu Zhang (MDPI AG, 2023)
We investigated the association of birthweight with overweight, obesity, and blood pressure (BP) among adolescents. This cross-sectional study included 857 participants aged 11-17 years from Liangshan, southwest China. Birthweight information was collected from the participants' parents. The participants' height, weight, and BP were measured. High birthweight was defined as a value greater than the sex-specific upper quartile. Participants were classified into four groups based on their weight change at birth and adolescence: normal weight at both time points, weight loss, weight gain, and high weight at both time points. High birthweight was positively associated with overweight and obesity in adolescence [odds ratio (95% confidence interval), OR (95% CI): 1.93 (1.33, 2.79)]. Compared with participants with normal weight at both time points, those with high weight at both time points were more likely to have elevated BP in adolescence (OR [95% CI]: 3.02 [1.65, 5.53]), while those with weight loss had similar odds of elevated BP. The sensitivity analysis results did not change significantly when high birthweight was defined alternatively as birthweight > 4 kg. This study showed that the association between high birthweight and elevated BP in adolescence is influenced by current weight.